Critical Role of TLR4 on the Microglia Activation Induced by Maternal LPS Exposure Leading to ASD-Like Behavior of Offspring - Xiao, Lu; Yan, Junyan; Feng, Di; Ye, Shasha; Yang, Ting; Wei, Hua; Li, Tingyu; Sun, Wuqing; Chen, Jie (Frontiers in Cell and Developmental Biology, 2021)
Objective: To investigate the role of TLR4 on the microglia activation in the pre-frontal cortex, which leads to autism-like behavior of the offspring induced by maternal lipopolysaccharide (LPS) exposure. Methods: Pregnant TLR4−/− (knockout, KO) and WT (wild type, WT) dams were intraperitoneally injected with LPS or PBS, respectively. The levels of TNFα, IL-1β, and IL-6 in the maternal serum and fetal brain were assessed with ELISA following LPS exposure. The gestation period, litter size and weight of the offspring were evaluated. Three-chamber sociability test, open field test and olfactory habituation/dishabituation test were used to assess the offspring's autism-like behavior at 7 weeks of age. Western blotting was performed to examine the levels of TLR4, Phospho-NFκB p65, IKKα, IBA-1, iNOS, Arg-1, C3, CR3A, NMDAR2A, and Syn-1 expression in the pre-frontal cortex. The morphological changes in the microglia, the distribution and expression of TLR4 were observed by immunofluorescence staining. Golgi-Cox staining was conducted to evaluate the dendritic length and spine density of the neurons in 2-week-old offspring. Results: Maternal LPS stimulation increased serum TNFα and IL-6, as well as fetal brain TNFα in the WT mice. The litter size and the weight of the WT offspring were significantly reduced following maternal LPS treatment. LPS-treated WT offspring had lower social and self-exploration behavior, and greater anxiety and repetitive behaviors. The protein expression levels of TLR4 signaling pathways, including TLR4, Phospho-NFκB p65, IKKα, and IBA-1, iNOS expression were increased in the LPS-treated WT offspring, whereas Arg-1 was decreased. Maternal LPS treatment resulted in the significant reduction in the levels of the synaptic pruning-related proteins, C3 and CR3A. Moreover, the neuronal dendritic length and spine density, as well as the expression levels of the synaptic plasticity-related proteins, NMDAR2A and Syn-1 were reduced in the WT offspring; however, gestational LPS exposure had no effect on the TLR4−/− offspring. Conclusion: Activation of TLR4 signaling pathway following maternal LPS exposure induced the abnormal activation of microglia, which in turn was involved in excessive synaptic pruning to decrease synaptic plasticity in the offspring. This may be one of the reasons for the autism-like behavior in the offspring mice.